Makna Visua Terhadap Kritik Kapitalisme Dalam FIlm: Kara, Anak Sebatang Pohon - Setia, Nandang Wahyu (Universitas Multimedia Nusantara, 2024)
Kara, Anak Sebatang Pohon (2005) is a short film with a story that reminds of the presence of capitalism in the social conditions of a family who lives very far from the crowds. The author is interested in researching this film because the story built by this film is critical of capitalism, and semiotics as a theory the author uses to analyze the process of sign formation and meaning production to see how media texts build their meaning. With the dichotomy of the sign system explained by Ferdinand De Sausurre, namely Signifier and Signified, whose relationship is an association between 'the signified' and 'the signifier', the author uses it to reveal the meaning of the series of symbols (signs) in the film This will be the presence of capitalism amidst the happiness of the life of a small family. Qualitative methodology and the Constructivist paradigm are used as a thought approach in looking at the unit of research analysis, namely the